Peri Perabun Remalan Bertungket: Communication Values Based on Local Wisdom of Gayo Culture - Irwansyah; Mesiono; Asnil Aida Ritonga (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to explore the philosophical and historical meaning behind the expression